Enhanced 5-hydroxytryptamine and dopamine-mediated behavioural responses following convulsions--II. The effects of anaesthesia and current conditions on the appearance of enhanced responses following electroconvulsive shock. - Cowen, P; Nutt, D; Green, A (1980)
Rats were given a single electroconvulsive shock (ECS; 125 V 1 sec, 50 Hz) under halothane anaesthesia or were given the anaesthetic only. Twenty-four hours later the behavioural changes which occurred after administration of either tranylcypromine (TCP; 5 mg/kg) followed by l-DOPA (25 mg/kg), or TCP followed by l-tryptophan (50 mg/kg), were similar in both groups. However enhanced responses following TCP/l-DOPA were seen 24 hr after a single ECS, when it was given to unanaethetised animals. Enhanced responses to TCP/l-DOPA but not to TCP/l-tryptophan were seen 24 hr following ECS given during halothane anaesthesia once daily for 5 days. The anaesthetic did not affect the responses of rats which were not subjected to ECS. When the rats were anaesthetised with methohexitone (5 mg/kg) a similar retardation of the appearance of enhanced behavioural responses was seen. This retardation does not appear to be due to the anaesthetics modifying the severity of the convulsion since administration of either methohexitone or halothane 1 hr after a single ECS to unanaesthetised animals also resulted in the animals not displaying enhanced responses to TCP/l-DOPA. Alteration of the ECS current conditions by increasing the voltage to 200 V (for 1 sec) or prolonging the time of the passage of current (125 V for 3 sec) did not result in any greater enhancement of the TCP/l-DOPA responses following ECS once daily for 5 days compared with animals given the 'standard' ECS (125 V, 1 sec). The data demonstrate that the number of ECS required to produce enhanced dopamine-mediated responses (TCP/l-DOPA) were less than those required for enhancement of 5-hydroxytryptamine-mediated responses (TCP/l-tryptophan) and that two dissimilar anaesthetics (halothane and methohexitone) retarded the appearance of the enhanced TCP/l-DOPA responses, not by modifying the convulsion but rather by interfering in some way with the mechanisms which occurred following the seizure. Increasing the length of seizure or the voltage passed did not appear to increase the enhancement of the behaviour.